A method for preparing ecological restoration materials from stone mine tailings
By processing stone mine tailings slag through mechanical grinding and high-temperature calcination, nano-silica particles are prepared and blended with activated porous cross-linked polystyrene to solve the problem of uneven dispersion of nano-silica and insufficient absorption capacity of macromolecular organic matter. problem, achieving efficient adsorption of heavy metals and organic matter, and simultaneous recovery of nano-silica particles.
Patent Information
- Application Number
- CN202410754666.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-06-12
AI Technical Summary
Silica particles in tailings slag in stone mines are difficult to disperse evenly, resulting in a decrease in adsorption capacity. Nanosilicon dioxide has weak absorption capacity on macromolecular organic matter and is difficult to recover.
Through mechanical grinding and high-temperature calcination, stone mine tailings slag is processed to prepare nano-silica particles with a particle size of 30-60 nm, and blended with activated porous cross-linked polystyrene to increase the adsorption surface area and organic matter adsorption capacity, while at the same time in nanometer The silica surface is grafted with EDTA to enhance the adsorption capacity of heavy metal ions.
It achieves uniform dispersion of nano-silica particles and efficient adsorption of heavy metals and organic matter, and because the network-structured polystyrene is easy to flocculate and settle, the nano-silica can be recycled simultaneously, resulting in high resource utilization.
Smart Images

Figure CN118718983B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparing ecological restoration materials from mine tailings, and in particular to a method for preparing ecological restoration materials from stone mine tailings. Background Art
[0002] After the original ore is processed by the selection operation, its main components have been enriched in the concentrate. After some of the ore is neutralized, the minor components or other associated metals of the ore are also recovered. The remaining products with very low useful components are called final tailings. The tailings of stone mines not only occupy a large area, but also have frequent strong winds in autumn. If the particles of some mine tailings are small, it is easy to cause air pollution. Therefore, it is necessary to make resource utilization of mine stone tailings.
[0003] There are many kinds of stone mine tailings, and their components mainly include SiO2, Fe2O3, CaO, MgO and Al2O3. SiO2 is often the most abundant component in tailings. In some areas, the content of SiO2 in stone mine tailings can even exceed 80%. The surface of silica particles can be used to absorb heavy metal ions in the environment after functionalization. For example, when silica particles are mixed with EDTA, the carboxyl and amino groups on them can absorb heavy metal ions and form stable chelates. According to this characteristic, tailings containing a large amount of silica can be used to prepare silica particles to absorb heavy metal ions in the environment and repair the ecological environment.
[0004] In order to improve the adsorption of heavy metal ions, a larger surface area is often required, and the tailings are often required to be prepared into nano-silicon dioxide. However, due to its small particle size, nano-silicon dioxide is prone to agglomeration when dispersed in water, resulting in a decrease in adsorption capacity, and its particle size is too small to be easily recovered from the environment. In addition, the surface pore size of nano-silicon dioxide is too small, and its ability to absorb large molecular organic matter in the environment is relatively weak. In response to the problems raised in the background technology above, technical personnel in this field have proposed an ecological restoration material using stone mine tailings as raw materials, which can efficiently absorb heavy metals and organic matter in the environment, and is evenly dispersed and easy to recycle, thereby realizing the resource utilization of stone mine tailings. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing ecological restoration materials from stone mine tailings to solve the problems raised in the above background technology.
[0006] In order to achieve the above purpose, the following technical solutions are provided:
[0007] A method for preparing ecological restoration materials from stone mine tailings, comprising the following steps:
[0008] S1: Mechanically grind the stone mine tailings and pass them through a 50-mesh sieve to obtain fine stone mine tailings;
[0009] S2: reacting the fine stone mine tailings obtained in step S1 with a hydrochloric acid solution, with mechanical stirring during the reaction, and the concentration of the hydrochloric acid used is 2 mol / L, filtering to obtain a filter residue after the reaction is completed, and washing the filter residue with deionized water;
[0010] S3: putting the filter residue obtained by washing in step S2 into a muffle furnace for calcination, reacting the calcined filter residue with a sodium hydroxide solution in a reactor, heating to 80-95° C. during the reaction, the reaction time is 2-3 hours, filtering out the filter residue, and obtaining a silicate solution;
[0011] S4: After cooling the silicate solution obtained in step S3, slowly add a 1 mol / L hydrochloric acid solution during stirring to adjust the pH of the solution to 6.2-7.2, a precipitate appears, the precipitate is filtered, washed with deionized water and then vacuum dried, and the obtained silica particles are ball-milled in a planetary ball mill to obtain nano-silicon dioxide;
[0012] S5: adding linear polystyrene to carbon tetrachloride, adding anhydrous aluminum chloride, stirring and heating to react for 3-4 hours, the heating temperature is 50-80°C, nitrogen is introduced into the solution during the reaction, and then deionized water and anhydrous ethanol are added to terminate the reaction, filtering the residue obtained by the reaction, washing it with ethanol, and then vacuum drying it to obtain cross-linked polystyrene;
[0013] S6: ultrasonically dispersing the cross-linked polystyrene obtained in step S5 into a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, stirring and reacting at 40-60° C. for 1-2.5 hours, filtering the solution after the reaction to obtain a filter residue, washing with ethanol, and drying to obtain activated porous cross-linked polystyrene;
[0014] S7: Ultrasonic dispersion of the activated porous cross-linked polystyrene obtained in step S6 and the nano-silica obtained in step S4 into anhydrous ethanol, stirring for 2 hours, adding 0.1 mol / L EDTA aqueous solution, heating to 40-65°C, and continuing to stir and react for 2-3 hours, filtering to obtain the residue, washing with ethanol, and vacuum drying to obtain the prepared ecological restoration material.
[0015] Furthermore, in step S3, the calcination temperature of the filter residue is 900-1100° C., and the calcination time of the filter residue in the muffle furnace is 3-5 hours.
[0016] Furthermore, the particle size of the nano-silicon dioxide obtained by ball milling in the planetary ball mill in step S4 is 30-60 nm.
[0017] Furthermore, in step S5, the mass ratio of linear polystyrene, carbon tetrachloride, anhydrous aluminum chloride, deionized water and anhydrous ethanol is 1:(40-140):(1-10):(8-60):(2-10).
[0018] Furthermore, in step S6, the concentration of concentrated sulfuric acid is 98wt%, the concentration of concentrated nitric acid is 60wt%, and the volume ratio of concentrated sulfuric acid to concentrated sulfuric acid is 1:2.
[0019] Furthermore, in step S7, the mass ratio of activated porous cross-linked polystyrene, nano-silica and anhydrous ethanol is 1:(1.4-1.7):(20-40), and the volume ratio of anhydrous ethanol to EDTA aqueous solution is 1:0.5.
[0020] Compared with the prior art, the beneficial effects of the present invention are:
[0021] 1. The present invention uses mine stone tailings as raw materials to prepare environmental repair materials, obtains nano-silicon dioxide particles with small particle size through mechanical grinding, high temperature and acid-base treatment, and grafts EDTA on the surface, which can effectively form stable chelates with heavy metal ions in water, not only effectively repairing the environment, but also saving resources;
[0022] 2. The nano-silicon dioxide prepared from the mine stone tailings as raw materials in the present invention is blended with activated cross-linked polystyrene, which not only effectively increases the overall surface area of the adsorption material, but also enables the composite material to have a strong adsorption capacity for organic matter;
[0023] 3. The present invention prepares cross-linked polystyrene with a mesh-like porous structure by reacting linear polystyrene with anhydrous aluminum chloride in carbon tetrachloride, thereby improving its adsorption capacity. The cross-linked polystyrene is further treated with concentrated nitric acid and concentrated sulfuric acid, and nitro and amino groups can be introduced to effectively activate the surface of the polystyrene, and further make the surface of the polystyrene rough and loose, so that the silicon dioxide with strong surface activity itself can be more easily and evenly loaded on the surface of the polystyrene, and can more easily adsorb organic matter and heavy metals in the sewage environment. At the same time, since the polystyrene with a mesh structure is more likely to flocculate and precipitate when adsorbing pollutants, it is easy to synchronously recover the nano silicon dioxide prepared by stone mine tailings added to the sewage environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a process flow chart of a method for preparing ecological restoration materials from stone mine tailings. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] See also Figure 1 , the present invention provides a technical solution:
[0027] Example 1
[0028] A method for preparing ecological restoration materials from stone mine tailings, comprising the following steps:
[0029] S1: Mechanically grind the stone mine tailings and pass them through a 50-mesh sieve to obtain fine stone mine tailings;
[0030] S2: reacting the fine stone mine tailings obtained in step S1 with a hydrochloric acid solution, with mechanical stirring during the reaction, and the concentration of the hydrochloric acid used is 2 mol / L, filtering to obtain a filter residue after the reaction is completed, and washing the filter residue with deionized water;
[0031] S3: putting the filter residue obtained by washing in step S2 into a muffle furnace for calcination at a temperature of 900° C. for a calcination time of 5 h, reacting the calcined filter residue with a sodium hydroxide solution in a reactor, heating to 80° C. for a reaction time of 3 h, filtering out the filter residue to obtain a silicate solution;
[0032] S4: After cooling the silicate solution obtained in step S3, a 1 mol / L hydrochloric acid solution is slowly added during stirring to adjust the pH of the solution to 6.2, and a precipitate is formed. The precipitate is filtered, washed with deionized water, and then vacuum dried. The obtained silica particles are ball-milled in a planetary ball mill to obtain nano-silicon dioxide with a particle size of 30 nm;
[0033] S5: adding linear polystyrene to carbon tetrachloride, adding anhydrous aluminum chloride, stirring and heating to react for 3 hours, the heating temperature is 80°C, nitrogen is introduced into the solution during the reaction, and then deionized water and anhydrous ethanol are added to terminate the reaction, the mass ratio of linear polystyrene, carbon tetrachloride, anhydrous aluminum chloride, deionized water and anhydrous ethanol is 1:40:1:8:2, filtering the residue obtained by the reaction, washing it with ethanol, and then vacuum drying to obtain cross-linked polystyrene;
[0034] S6: ultrasonically dispersing the cross-linked polystyrene obtained in step S5 into a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, stirring and reacting at 40° C. for 2.5 hours, wherein the concentration of the concentrated sulfuric acid is 98wt%, the concentration of the concentrated nitric acid is 60wt%, and the volume ratio of the concentrated sulfuric acid to the concentrated sulfuric acid is 1:2, and the residue obtained by filtering the solution after the reaction is washed with ethanol and dried to obtain activated porous cross-linked polystyrene;
[0035] S7: Ultrasonic disperse the 20 g activated porous cross-linked polystyrene obtained in step S6 and the 28 g nano-silica obtained in step S4 into 400 g anhydrous ethanol, stir for 2 h, add 240 ml 0.1 mol / L EDTA aqueous solution, heat to 40°C and continue stirring for 3 h, filter the residue, wash with ethanol and vacuum dry to obtain the prepared ecological restoration material.
[0036] Example 2
[0037] A method for preparing ecological restoration materials from stone mine tailings, comprising the following steps:
[0038] S1: Mechanically grind the stone mine tailings and pass them through a 50-mesh sieve to obtain fine stone mine tailings;
[0039] S2: reacting the fine stone mine tailings obtained in step S1 with a hydrochloric acid solution, with mechanical stirring during the reaction, and the concentration of the hydrochloric acid used is 2 mol / L, filtering to obtain a filter residue after the reaction is completed, and washing the filter residue with deionized water;
[0040] S3: putting the filter residue obtained by washing in step S2 into a muffle furnace for calcination at a temperature of 1100° C. for 3 hours, reacting the calcined filter residue with a sodium hydroxide solution in a reactor, heating the reaction to 95° C. for 2 hours, filtering out the filter residue to obtain a silicate solution;
[0041] S4: After cooling the silicate solution obtained in step S3, a 1 mol / L hydrochloric acid solution is slowly added during stirring to adjust the pH of the solution to 7.2, and a precipitate is formed. The precipitate is filtered, washed with deionized water, and then vacuum-dried. The obtained silica particles are ball-milled in a planetary ball mill to obtain nano-silicon dioxide with a particle size of 60 nm;
[0042] S5: adding linear polystyrene to carbon tetrachloride, adding anhydrous aluminum chloride, stirring and heating to react for 4 hours, the heating temperature is 50°C, nitrogen is introduced into the solution during the reaction, and then deionized water and anhydrous ethanol are added to terminate the reaction, the mass ratio of linear polystyrene, carbon tetrachloride, anhydrous aluminum chloride, deionized water and anhydrous ethanol is 1:140:10:60:10, filtering the residue obtained by the reaction, washing it with ethanol and then vacuum drying it to obtain cross-linked polystyrene;
[0043] S6: ultrasonically dispersing the cross-linked polystyrene obtained in step S5 into a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, stirring and reacting at 60° C. for 1 h, wherein the concentration of the concentrated sulfuric acid is 98wt%, the concentration of the concentrated nitric acid is 60wt%, and the volume ratio of the concentrated sulfuric acid to the concentrated sulfuric acid is 1:2, and the residue obtained by filtering the solution after the reaction is washed with ethanol and dried to obtain activated porous cross-linked polystyrene;
[0044] S7: Ultrasonic disperse the 20 g activated porous cross-linked polystyrene obtained in step S6 and the 34 g nano-silica obtained in step S4 into 800 g anhydrous ethanol, stir for 2 h, add 480 ml 0.1 mol / L EDTA aqueous solution, heat to 40-65°C and continue to react for 2-3 h, filter the residue, wash with ethanol and vacuum dry to obtain the prepared ecological restoration material.
[0045] Example 3
[0046] A method for preparing ecological restoration materials from stone mine tailings, comprising the following steps:
[0047] S1: Mechanically grind the stone mine tailings and pass them through a 50-mesh sieve to obtain fine stone mine tailings;
[0048] S2: reacting the fine stone mine tailings obtained in step S1 with a hydrochloric acid solution, with mechanical stirring during the reaction, and the concentration of the hydrochloric acid used is 2 mol / L, filtering to obtain a filter residue after the reaction is completed, and washing the filter residue with deionized water;
[0049] S3: putting the filter residue obtained by washing in step S2 into a muffle furnace for calcination at a temperature of 1000° C. for a calcination time of 4.2 h, reacting the calcined filter residue with a sodium hydroxide solution in a reactor, heating to 90° C. during the reaction, and reacting for 2.6 h, filtering out the filter residue to obtain a silicate solution;
[0050] S4: After cooling the silicate solution obtained in step S3, a hydrochloric acid solution with a concentration of 1 mol / L is slowly added during stirring to adjust the pH of the solution to 7, and a precipitate is formed. The precipitate is filtered, washed with deionized water, and then vacuum dried. The obtained silica particles are ball-milled in a planetary ball mill to obtain nano-silicon dioxide with a particle size of 50 nm;
[0051] S5: adding linear polystyrene to carbon tetrachloride, adding anhydrous aluminum chloride, stirring and heating to react for 3.6 hours, the heating temperature is 70°C, nitrogen is introduced into the solution during the reaction, and then deionized water and anhydrous ethanol are added to terminate the reaction, the mass ratio of linear polystyrene, carbon tetrachloride, anhydrous aluminum chloride, deionized water and anhydrous ethanol is 1:100:8:35:8, filtering the residue obtained by the reaction, washing it with ethanol and then vacuum drying it to obtain cross-linked polystyrene;
[0052] S6: ultrasonically dispersing the cross-linked polystyrene obtained in step S5 into a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, stirring and reacting at 50° C. for 2 h, wherein the concentration of the concentrated sulfuric acid is 98wt%, the concentration of the concentrated nitric acid is 60wt%, and the volume ratio of the concentrated sulfuric acid to the concentrated sulfuric acid is 1:2, and the residue obtained by filtering the solution after the reaction is washed with ethanol and dried to obtain activated porous cross-linked polystyrene;
[0053] S7: Ultrasonic disperse the 20 g activated porous cross-linked polystyrene obtained in step S6 and the 30 g nano-silica obtained in step S4 into 600 g anhydrous ethanol, stir for 2 h, add 360 ml 0.1 mol / L EDTA aqueous solution, heat to 60°C and continue to react for 2.8 h, filter the residue, wash with ethanol and vacuum dry to obtain the prepared ecological restoration material.
[0054] Comparative Example 1
[0055] The difference between Comparative Example 1 and Example 1 is that step S6 is omitted, thereby canceling the cross-linking treatment of polystyrene, and the other steps are exactly the same as Example 1. The linear polystyrene in Comparative Example 1 is treated with concentrated nitric acid and concentrated sulfuric acid and then directly blended with nano-silicon dioxide and EDTA prepared from stone mine tailings.
[0056] Comparative Example 2
[0057] The difference between Comparative Example 2 and Example 1 is that step S7 is omitted, thereby eliminating the step of treating the cross-linked polystyrene with concentrated nitric acid and concentrated sulfuric acid. The other steps are exactly the same as those in Example 1. In Comparative Example 2, after cross-linking, the linear polystyrene is directly blended with nano-silicon dioxide and EDTA prepared from stone mine tailings.
[0058] Comparative Example 3
[0059] The difference between Comparative Example 3 and Example 1 is that both step S6 and step S7 are omitted, thereby canceling the crosslinking and concentrated acid treatment steps of the linear polystyrene, and the other steps are exactly the same as those in Example 1. The linear polystyrene in Comparative Example 3 is directly blended with nano-silicon dioxide and EDTA prepared from stone mine tailings.
[0060] Six ecological restoration materials were prepared through the above six implementation methods. Under laboratory environmental conditions, 100 mg / L of Pb 2+ Cr 2+ , Cu 2+ and Hg 2+ nitrate solution, each nitrate solution was prepared in six portions, each nitrate solution was 100 ml, the pH of the solution was adjusted to 7, the above nitrate solutions were mixed with the ecological restoration materials prepared in the above six embodiments, the ecological restoration materials added to each nitrate solution were 5 g, after reacting for 15 minutes, the remaining metal particle content in the nitrate solution was calculated, and the removal rate (R / %) was calculated. The results are shown in Table 1 below:
[0061] Table 1: Heavy metal ion removal rate (R / %)
[0062] <![CDATA[Pb 2+ ]]> <![CDATA[Cr 2+ ]]> <![CDATA[Cu 2+ ]]> <![CDATA[Hg 2+ ]]> Example 1 87.5 79.3 71.5 75.3 Example 2 91.2 82.1 72.8 76.4 Example 3 89.5 78.4 74.3 72.4 Comparative Example 1 79.3 65.4 56.2 60.8 Comparative Example 2 78.2 66.7 51.3 61.5 Comparative Example 3 69.8 59.8 41.1 50.7
[0063] As shown in Table 1 above, the ecological restoration material prepared by the present invention has a significant effect on the heavy metal Pb in water. 2+ Cr 2+ , Cu 2+ and Hg 2+ It has a very good removal effect, and the removal rate of the above four heavy metal ions can reach more than 70%. Some heavy metal ions such as Pb 2+ It can even reach a removal rate of more than 90%. When linear polystyrene is only treated with concentrated acid or cross-linked, the removal rate is significantly reduced. When there is no concentrated acid treatment or cross-linking treatment, the direct use of linear polystyrene and nano-silica blending further reduces the ability to treat heavy metal ions.
[0064] Under laboratory environmental conditions, 100 mg / L phenol, o-hydroxybenzoic acid and p-nitroaniline solutions were prepared respectively, six portions of each nitrate solution were prepared, each portion of the nitrate solution was 100 ml, the pH of the solution was adjusted to 7, the above solutions were mixed with the ecological restoration materials prepared in the above six embodiments, 5 g of ecological restoration materials were added to each nitrate solution, and after 15 minutes of reaction, the residual content of phenol, o-hydroxybenzoic acid and p-nitroaniline in each solution was calculated, and the removal rate (R / %) was calculated. The results are shown in Table 2 below:
[0065] Table 2: Organic matter removal rate (R / %)
[0066]
[0067] It can be seen from Table 2 above that the ecological restoration material prepared by the embodiment of the present invention has a very good removal effect on the organic matter of phenol, o-hydroxybenzoic acid and p-nitroaniline in water, and the removal rate of the three organic matters is more than 80%. However, when the linear polystyrene is only treated with concentrated acid or only cross-linked, or is not treated with both, its adsorption capacity for organic matter shows a cliff-like decline.
[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing ecological restoration materials from stone mine tailings, characterized in that: The following steps are involved: S1: Mechanically grind the stone mine tailings and pass them through a 50-mesh sieve to obtain fine stone mine tailings; S2: reacting the fine stone mine tailings obtained in step S1 with a hydrochloric acid solution, with mechanical stirring during the reaction, and the concentration of the hydrochloric acid used is 2 mol / L, filtering to obtain a filter residue after the reaction is completed, and washing the filter residue with deionized water; S3: putting the filter residue obtained by washing in step S2 into a muffle furnace for calcination, reacting the calcined filter residue with a sodium hydroxide solution in a reactor, heating to 80-95° C. during the reaction, the reaction time is 2-3 hours, filtering out the filter residue, and obtaining a silicate solution; S4: After cooling the silicate solution obtained in step S3, slowly add a 1 mol / L hydrochloric acid solution during stirring to adjust the pH of the solution to 6.2-7.2, a precipitate appears, the precipitate is filtered, washed with deionized water and then vacuum dried, and the obtained silica particles are ball-milled in a planetary ball mill to obtain nano-silicon dioxide; S5: adding linear polystyrene to carbon tetrachloride, adding anhydrous aluminum chloride, stirring and heating to react for 3-4 hours, the heating temperature is 50-80°C, nitrogen is introduced into the solution during the reaction, and then deionized water and anhydrous ethanol are added to terminate the reaction, filtering the residue obtained by the reaction, washing it with ethanol, and then vacuum drying it to obtain cross-linked polystyrene; S6: ultrasonically dispersing the cross-linked polystyrene obtained in step S5 into a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid, stirring and reacting at 40-60° C. for 1-2.5 hours, filtering the solution after the reaction to obtain a filter residue, washing with ethanol, and drying to obtain activated porous cross-linked polystyrene; S7: ultrasonically dispersing the activated porous cross-linked polystyrene obtained in step S6 and the nano-silica obtained in step S4 into anhydrous ethanol, stirring for 2 hours, adding 0.1 mol / L EDTA aqueous solution, heating to 40-65° C., and continuing stirring for 2-3 hours, filtering to obtain the residue, washing with ethanol, and vacuum drying to obtain the prepared ecological restoration material; In step S7, the mass ratio of activated porous cross-linked polystyrene, nano-silica and anhydrous ethanol is 1:(1.4-1.7):(20-40), and the volume ratio of anhydrous ethanol to EDTA aqueous solution is 1:0.
5.
2. The method for preparing ecological restoration materials from stone mine tailings according to claim 1, characterized in that: In step S3, the calcination temperature of the filter residue is 900-1100° C., and the calcination time of the filter residue in the muffle furnace is 3-5 hours.
3. The method for preparing ecological restoration materials from stone mine tailings according to claim 1, characterized in that: The particle size of the nano-silicon dioxide obtained by ball milling with a planetary ball mill in step S4 is 30-60 nm.
4. The method for preparing ecological restoration materials from stone mine tailings according to claim 1, characterized in that: In the step S5, the mass ratio of linear polystyrene, carbon tetrachloride, anhydrous aluminum chloride, deionized water and anhydrous ethanol is 1:(40-140):(1-10):(8-60):(2-10).
5. The method for preparing ecological restoration materials from stone mine tailings according to claim 1, characterized in that: In step S6, the concentration of concentrated sulfuric acid is 98wt%, the concentration of concentrated nitric acid is 60wt%, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 1:2.
Citation Information
Patent Citations
Method for preparing SiO2 / polystyrene composite porous material for oil-water separation
CN110423298A
Composite Polymer-Coated Sorbent with a Bidisperse Pore Size Distribution for the Simultaneous Separation and Desalting of Biopolymers
US20070293394A1
Cited By
Method for reconstructing soil through synergy of sugar refining by-products and tailings
CN121797714A